Toxicity of Bothrops neuwiedi complex (“yarará chica”) venom from different regions of Argentina (Serpentes, Viperidae) - de Oliveira, Vanessa Costa (2011)
Fil: de Oliveira, Vanessa Costa. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Producción de Biológicos; Argentina.